Penerapan Bela Negara Di Era Teknologi Maju Dalam Pembelajaran Pendidikan Kewarganegaraan Pada Siswa Sekolah Dasar - Luh Putu, Swandewi Antari; I Putu Karpika (Elementary Teacher Education Program, Majalengka University, 2023)
State defense is a concept contained in a country's laws and regulations regarding the patriotism of a person or group of people in a country. This study aims to determine the application of state defense in the era of advanced technology in learning civics education in elementary school students. Research methods that. used. This research is a qualitative research method, using, the questionnaire method. The location in this study is located in Denpasar, Bali. Research informants used purposive sampling by selecting informants, namely students from an elementary school in Denpasar. Research data was collected using a questionnaire filled in by respondents through the media and data collection techniques. In a country every citizen is obliged to defend the country, where defending the country is a form of citizen's love for their homeland for their country, especially instilling an attitude of defending the country among the younger generation who have been battered by technological advances.